IS IT ILLEGAL FOR FOREIGN VESSELS TO TRANSIT THROUGH INDONESIAN WATERS WITHOUT UTILIZING THE ARCHIPELAGIC SEA LANES? - Nugroho, Sigit Sutadi (Jurnal Bina Mulia Hukum, 2023)
This paper addresses the question of whether foreign vessels can infringe upon their transit through Indonesian waters without using the Indonesian Archipelagic Sea Lanes. To answer this question, the paper discusses the concept of transit rights, including innocent passage rights, transit passage rights, and archipelagic sea lanes passage rights, as well as the prohibitions and obligations of foreign vessels in exercising archipelagic sea lanes passage rights as stipulated by international and national legal provisions. This research is conducted in a normative manner, utilizing a literature review as the data collection method, and consequently employing secondary data. The analysis technique applied is content analysis. This paper concludes that despite the establishment of the Indonesian archipelagic sea lanes, it does not imply that foreign vessels must necessarily traverse these sea lanes when transiting through Indonesian waters. Foreign vessels engaged in transit have the right to peacefully navigate through Indonesian waters, provided they respect and comply with the domestic regulations of the archipelagic state and international law.